A new species of Regimbartia Zaitzev, 1908 and additional faunistic records of Regimbartia attenuata (Fabricius, 1801) from China (Coleoptera, Hydrophilidae, Hydrophilinae). Issue 3 (26th August 2022) - Mai, Zuqi; Hu, Jian; Jia, Fenglong; Jäch, Manfred A.
Abstract: A new species of the water scavenger beetle, Regimbartia majorobtusa Mai, Jia, and Jäch sp. n., is described from China (Yunnan) and Thailand (Phitsanulok). It is the eleventh known species of this genus. Regimbartia attenuata (Fabricius, 1801 ) is redescribed; it is reported for the first time from the Chinese provinces Shaanxi and Hubei. A key to the Chinese species of the genus Regimbartia Zaitzev, 1908 is provided, and the two remaining Asian species, R. minima Orchymont, 1941 and R. sumatrensis Orchymont, 1941, are diagnosed. http://www.zoobank.org/urn:lsid:zoobank.org:pub:992D271C-3327-4706-8625-7662CA4E2EF4